Community-Based Strategies for Perinatal Mental Health Services in Low-middle Income Countries: Scoping Review - Ammalia, Septiana Ade (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
Introduction: Perinatal mental health is critical to the well-being of both mother and child, influencing maternal quality of life and child development. Community-based approaches have proven effective in enhancing service accessibility and quality while also reducing maternal morbidity. Objective: This scoping review aims to identify and explore scientific evidence regarding strategies for delivering community-based perinatal mental health services in developing countries. Method: This study employed a scoping review design guided by the Population–Concept–Context (PCC) framework. Literature searches were conducted across PubMed, ScienceDirect, Cochrane Library, EBSCO, and gray literature sources, including Google Scholar. Selected articles were critically appraised using the JBI Critical Appraisal Tools and the Mixed Methods Appraisal Tool (MMAT).Results: Out of 726 records screened, 10 articles met the inclusion and exclusion criteria. The analysis revealed four central themes: (1) community-based mental health service strategies, (2) instruments used to detect perinatal mental health disorders, (3) enabling and limiting factors in implementing community-based services, and (4) the benefits of community-based mental health interventions. Conclusion: Community-based mental health strategies are widely adopted in developing countries to address service gaps, particularly in settings with limited resources and access. However, challenges such as insufficient policy support, inadequate funding, limited training for healthcare providers, and persistent social stigma continue to hinder effective implementation.